Systematic Literature Review : Tantangan dan Peluang Penerapan Pajak Digital di Indonesia - Anisa Dwi Wahyuni; Rizki Indrawan (STIKes Ibnu Sina Ajibarang, 2025)
The development of the digital economy in Indonesia, particularly through social media and digital platforms, presents new challenges in the national taxation system. This study aims to review the digital taxation policies that have been implemented, identify challenges and opportunities, and analyze their impact on tax compliance and revenue. The method used is Systematic Literature Review (SLR) of 25 scientific articles published between 2019 and 2024. The study results show that Indonesia has implemented digital tax policies through regulations such as Income Tax and VAT on digital transactions as well as self-assessment and withholding reporting systems. Key challenges include low tax awareness and compliance, lack of education, regulatory complexity, and limited oversight. Nonetheless, there are great opportunities to increase state revenue through the use of technology, broadening the tax base, and international collaboration. The impact on tax compliance is not optimal, but can be improved with the right strategies, including education and administrative reform. This study recommends strengthening the regulatory framework, inter-agency synergy, and technology utilization as strategic steps to support the successful implementation of digital tax in Indonesia.